BEHAVIORAL FACTORS AFFECTING PERSONAL FINANCIAL MANAGEMENT AND SAVINGS HABITS: A CASE STUDY OF GEN Z - Hidayat, Gustina; Hermawan, Atang (Faculty of Economic and Business, University of Pasundan, 2025)
This study explores the influence of behavioral factors—self-control, financial anxiety, overconfidence, mental accounting, and future orientation—on personal financial management and savings habits, with financial literacy examined as a moderating factor. Using a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, data were collected from a diverse sample of individuals to assess how these behavioral traits shape financial behaviors. The results reveal that self-control, mental accounting, and future orientation positively impact financial management, while financial anxiety negatively affects it. Overconfidence was also found to positively influence financial management, though it may carry risks when unchecked. Financial management, in turn, has a significant positive effect on savings habits. Financial literacy significantly moderates the relationship between these behavioral factors and financial management, particularly strengthening the effects of self-control, overconfidence, mental accounting, and future orientation. This study highlights the importance of integrating behavioral insights and financial education to promote effective financial management and savings behavior. The findings offer practical implications for financial education programs, policymakers, and financial institutions seeking to improve individuals' financial well-being.